Meta Analisis: Pengaruh Media Pembelajaran terhadap Hasil Belajar Matematika Peserta Didik - Baqi, Muh.; Tayeb, Thamrin; Nur, Fitriani; Majid, Ahmad Farham; Mattoliang, Lisnasari Andi (Al Asma: Journal of Islamic Education, 2023)
Improving the quality of mathematics learning is an urgent need in education. One factor that plays a crucial role in the learning process is the use of learning media. This research aims to find out (1) the type of media that influences overall mathematics learning, (2) the summary effect size of the application of learning media that influences students' mathematics learning outcomes, and (3) whether the application of learning media influences students' mathematics learning outcomes. This type of research is meta-analysis, which is a study that uses data from previous research to be analyzed systematically and quantitatively in order to obtain comprehensive conclusions regarding the results of the research being studied. Data collection was carried out by searching for articles that were relevant to the topic being studied on internet network sites such as Google Scholar, Research Gate, One Search, Open Knowledge Map, Eric, IPI Search, and Microsoft Academic, using the keywords the influence of learning media on student learning outcomes. The samples analyzed are research reports that meet the predetermined sample criteria. The instruments used are data collection sheets, screening sheets, and feasibility sheets. Data analysis techniques use descriptive and inferential statistics. This research found that the most influential media was print media; the summary effect size was 0.636, which is within the criteria for a large high effect size, and the hypothesis test results showed that learning media had a significant effect on student learning outcomes.